THE INFLUENCE OF ISLAMIC CORPORATE GOVERNANCE ON THE PERFORMANCE OF SHARIA BANKS: AN EMPIRICAL STUDY OF INDONESIA AND MALAYSIA - Faris Achmad Muhtadin Billah; Bayu Arie Fianto (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh karakteristik Islamic corporate governance terhadap kinerja bank syariah di Indonesia dan Malaysia. Dengan menggunakan regresi data panel 28 bank syariah di Indonesia dan Malaysia periode 2013-2019, penelitian ini menemukan adanya pengaruh Islamic corporate governance (ICG) secara simultan terhadap kinerja bank syariah. Hasil estimasi dengan dan tanpa variabel kontrol menunjukkan hanya variabel tingkat pendidikan Dewan Pengawas Syariah (DPS) yang konsisten memiliki pengaruh negatif signifikan terhadap kinerja bank syariah. Dengan menambahkan variabel kontrol, hasil penelitian menunjukkan bahwa variabel gender diversity dan frekuensi rapat DPS masing-masing berpengaruh positif dan negatif terhadap kinerja bank syariah. Hasil penelitian ini memberikan wawasan bagi regulator untuk dapat meningkatkan kinerja bank syariah melalui praktik ICG. Kata Kunci: Bank syariah, Dewan Pengawas Syariah, Indonesia, Islamic corporate governance, Kinerja bank, Malaysia. ABSTRACTThis study aims to determine the impact of Islamic corporate governance characteristics on the performance of Islamic banks in Indonesia and Malaysia. By using panel data regression of 28 Islamic banks in Indonesia and Malaysia for the 2013-2019 period, this study found the simultaneous influence of Islamic corporate governance (ICG) characteristics on the performance of Islamic banks. The results with and without control variables show that only the Sharia Supervisory Board (SSB) education level consistently has a significant negative effect on the performance of Islamic banks. By adding the control variable, the results show that the gender diversity variable and the frequency of SSB meetings have a positive and negative effect on the performance of Islamic banks, respectively. The results of this study provide insights for regulators to improve the performance of Islamic banks through ICG practices.Keywords: Bank performance, Indonesia, Islamic corporate governance, Islamic banks, Malaysia, Syariah Supervisory Board. DAFTAR PUSTAKAAgrawal, N., & Lakshmi, V. (2020). Board composition and board size impact on financial performance of the company. International Journal of Public Sector Performance Management, 6(5), 737–747. https://doi.org/10.1504/IJPSPM.2020.110142Ajili, H., & Bouri, A. (2018). Corporate governance quality of Islamic banks: measurement and effect on financial performance. International Journal of Islamic and Middle Eastern Finance and Management, 11(3), 470–487. https://doi.org/10.1108/IMEFM-05-2017-0131Alam, N., & Homy, A. (2020). The impact of corporate governance and agency effect on earnings management – A test of the dual banking system. Research in International Business and Finance, 54(April), 1–16.Al-Jaifi, H. A. (2020). Board gender diversity and environmental, social and corporate governance performance: evidence from ASEAN banks. Asia-Pacific Journal of Business Administration, 12(3–4), 269–281. https://doi.org/10.1108/APJBA-12-2018-0222Alsartawi, A. M. (2019). Performance of Islamic banks: Do the frequency of shariʿah supervisory board meetings and independence matter?. ISRA International Journal of Islamic Finance, 11(2), 303–321. https://doi.org/10.1108/IJIF-05-2018-0054Aslam, E., & Haron, R. (2020). Does corporate governance affect the performance of Islamic banks? New insight into Islamic countries. Corporate Governance, 20(6), 1073–1090. https://doi.org/10.1108/CG-11-2019-0350Baklouti, I. (2020). Is the sharia supervisory board a friend or an enemy of Islamic banks? Journal of Islamic Marketing. https://doi.org/10.1108/JIMA-04-2020-0118Baltagi, B. H. (2005). Econometric analysis of panel data, 3rd ed. New York: John Wiley & Sons.Bank Negara Malaysia. (2013). Guidelines on corporate governance for licensed institutions - BNM/RH/GL 001-1. Diakses dari https://www.bnm.gov.my/documents/20124/761709/20130619_B_PL_0014.pdfBank Negara Malaysia. (2016). Policy document on corporate governance - BNM/RH/PD 029-9. Diakses dari https://www.bnm.gov.my/documents/20124/65319/pd_CorporateGovernance_Aug2016.pdfBouteska, A. (2020). Do board characteristics affect bank performance? Evidence from the Eurozone. Journal of Asset Management, 21(6), 535–548. https://doi.org/10.1057/s41260-020-00181-2Buallay, A. (2019). Corporate governance, shari’ah governance and performance. International Journal of Islamic and Middle Eastern Finance and Management, 12(2), 216–235. https://doi.org/10.1108/IMEFM-07-2017-0172Choudhury, M. A. (2013). Corporate governance in Islamic perspective. International Journal of Islamic and Middle Eastern Finance and Management, 6(3), 180–199. https://doi.org/10.1108/IMEFM-10-2012-0101Darwanto, C. A. (2019). Corporate governance and financial performance in Islamic banks: The role of the sharia supervisory board in multiple-layer management. Banks and Bank Systems, 14(4), 183–191.De Haan, J., & Vlahu, R. (2016). Corporate governance of banks: A survey. Journal ofEconomic Surveys, 30(2), 228–277. https://doi.org/10.1111/joes.12101.Farag, H., Mallin, C., & Ow-yong, K. (2018). Corporate governance in Islamic banks: New insights for dual board structure and agency relationships. Journal of International Financial Markets, Institutions & Money, 54, 59–77.Fuzi, S. F. S., Halim, S. A. A., & Julizaerma, M. K. (2016). Board independence and firm performance. Procedia Economics and Finance, 37(16), 460–465. https://doi.org/10.1016/s2212-5671(16)30152-6Hakimi, A., Rachdi, H., Rim, B. S. M., & Hssini, H. (2018). Do board characteristics affect bank performance? Evidence from the Bahrain Islamic banks. Journal of Islamic Accounting and Business Research, 9(2), 251–272. https://doi.org/10.1108/JIABR-06-2015-0029Peraturan Bank Indonesia Nomor 11/33 Tahun 2009.Isa, M., & Lee, S. P. (2020). Does the shariah committee influence risk-taking and performance of Islamic banks in Malaysia? Journal of Islamic Accounting and Business Research, 11(9), 1739–1755. https://doi.org/10.1108/JIABR-12-2018-0207Iskandar, B. A., & Laila, N. (2016). Pengaruh komponen risk-based bank rating terhadap profitabilitas bank umum syariah di Indonesia (Periode 2011–2014). Jurnal Ekonomi Syariah Teori dan Terapan, 3(3), 173–186Islamic Financial Services Board. (2009). Guiding principles on shariah governance systems for institutions offering Islamic financial services. Diakses dari https://ifsb.org/download.php?id=4366&lang=English&pg=/published.phpJungmann, C. (2006). The effectiveness of corporate governance in one-tier and two-tier board systems: Evidence from the UK and Germany. European Company and Financial Law Review, 3(4). https://doi.org/10.1515/ecfr.2006.019Khalil, A., & Boulila, T. N. (2020). The impact of the shariah board’s characteristics on the financial soundness of Islamic banks. Journal of Islamic Accounting and Business Research. https://doi.org/10.1108/JIABR-08-2018-0127Khan, I., & Zahid, S. N. (2020). The impact of shari’ah and corporate governance on Islamic banks performance: evidence from Asia. International Journal of Islamic and Middle Eastern Finance and Management, 13(3), 483–501. https://doi.org/10.1108/IMEFM-01-2019-0003Lassoued, M. (2018). Corporate governance and financial stability in Islamic banking. Managerial Finance, 44(5), 524–539. https://doi.org/10.1108/MF-12-2016-0370Mansour, W., & Bhatti, M. I. (2018). The new paradigm of Islamic corporate governance. Managerial Finance, 44(5), 513-523. https://doi.org/10.1108/MF-01-2018-0043Mayur, M., & Saravanan, P. (2017). Performance implications of board size, composition and activity: Empirical evidence from the Indian banking sector. Corporate Governance (Bingley), 17(3), 466–489. https://doi.org/10.1108/CG-03-2016-0058Mazzotta, R., & Ferraro, O. (2020). Does the gender quota law affect bank performances? Evidence from Italy. Corporate Governance (Bingley), 20(6), 1135–1158. https://doi.org/10.1108/CG-08-2019-0252Meslier, C., Risfandy, T., & Tarazi, A. (2020). Islamic banks equity financing, shariah supervisory board, and banking environments. Pacific-Basin Finance Journal, 62. https://doi.org/https://doi.org/10.1016/j.pacfin.2020.101354Mishra, S. (2020). Do independent directors improve firm performance? Evidence from India. Global Business Review, 1-19. https://doi.org/10.1177/0972150920917310Mollah, S., Hassan, M. K., Al Farooque, O., & Mobarek, A. (2017). The governance, risk-taking, and performance of Islamic banks. Journal of Financial Services Research, 51, 195–219. https://doi.org/10.1007/s10693-016-0245-2Mollah, S., & Zaman, M. (2015). Shari’ah supervision, corporate governance and performance: Conventional vs Islamic banks. Journal of Banking & Finance, 58, 418–435. https://doi.org/10.1016/j.jbankfin.2015.04.030Moundigbaye, M., Rea, W. S., & Reed, W. R. (2018). Which panel data estimator should I use? Economics: The Open-Access, Open-Assessment E-Journal, 12(4). https://doi.org/10.1080/00036840802600087Nomran, N. M., & Haron, R. (2019). Dual board governance structure and multi-bank performance: A comparative analysis between Islamic banks in Southeast Asia and GCC countries. Corporate Governance (Bingley), 19(6), 1377–1402. https://doi.org/10.1108/CG-10-2018-0329Nomran, N. M., & Haron, R. (2020a). Shari’ah supervisory board’s size impact on performance in the Islamic banking industry: An empirical investigation of the optimal board. Journal of Islamic Accounting and Business Research, 11(1), 110–129. https://doi.org/10.1108/JIABR-05-2017-0070Nomran, N. M., & Haron, R. (2020b). A systematic literature review on Shari’ah governance mechanism and firm performance in Islamic banking. Islamic Economic Studies, 27(2), 91–123. https://doi.org/10.1108/IES-06-2019-0013Nomran, N. M., Haron, R., & Hassan, R. (2018). Shari’ah supervisory board characteristics effects on Islamic banks’ performance: Evidence from Malaysia. International Journal of Bank Marketing, 36(2), 290–304. https://doi.org/10.1108/IJBM-12-2016-0197Nurkhin, A., Rohman, A., & Rofiq, A. (2018). The role of the sharia supervisory board and corporate governance mechanisms in enhancing Islamic performance – evidence from Indonesia. Banks and Bank Systems, 13(4), 85–95. https://doi.org/10.21511/bbs.13(4).2018.08OJK. (2014). Surat Edaran Otoritas Jasa Keuangan Nomor 10/SEOJK.03/2014.OJK. (2014). Peraturan Otoritas Jasa Keuangan No. 33/PJOK.04/2014.Permatasari, I. (2020). Does corporate governance affect bank risk management? Case study of Indonesian banks. International Trade, Politics and Development. https://doi.org/10.1108/itpd-05-2020-0063Safieddine, A. (2009). Islamic financial institutions and corporate governance: New insights for agency theory. Corporate Governance: An International Review, 17(2), 142–158. https://doi.org/10.1111/j.1467-8683.2009.00729.xSafiullah, M. D., Hassan, M. K., & Kabir, M. N. (2020). Corporate governance and liquidity creation nexus in Islamic banks—Is managerial ability a channel?. Global Finance Journal, In Press, Corrected Proof. https://doi.org/10.1016/j.gfj.2020.100543Sugiyono. (2019). Metode penelitian kuantitatif, kualitatif dan R&D. Bandung: CV. Alfabeta.Trinh, V. Q., Elnahass, M., Salama, A., & Izzeldin, M. (2019). Board busyness, performance and financial stability: Does bank type matter? European Journal of Finance, 26(7–8), 774–801. https://doi.org/10.1080/1351847X.2019.1636842Wooldridge, J. M. (2010). Econometric analysis of cross section and panel data, 2nd ed. Cambridge, Massachusetts: The MIT Press.Zeineb, G. B., & Mensi, S. (2018). Corporate governance, risk and efficiency: Evidence from GCC Islamic banks. Managerial Finance, 44(5), 551–569. https://doi.org/10.1108/MF-05-2017-0